Inclusion As Human Right Is Not Assured Yet at the Autonomous University of Baja California - Plazola Rivera, Carmen Amalia (2019)
Even though it is true that our university has been trying to reach inclusion, this is not achieved yet. We are talking about the inclusion of disabled people; notwithstanding that the institution has accepted them, it has not been able to grant them the guarantee of that inclusion, violating with this what the Constitution establishes in its first article, “It is prohibited all kinds of discrimination due to ethnic origin or nationality, gender, age, disabilities, social condition, health conditions, religion, opinions, sexual preferences, marital status, or any other condition that is considered as a violation of human dignity or targets to destroy or reduce people’s rights and freedoms.” So, we consider a severe violation of human dignity of disabled people, since they do not find true adaptation to their needs in our educative institution. Integrating disabled people is not possible just with signs in the premises and simply building ramps for them. Our university has tried this but has not reached the true inclusion of its infrastructure to this challenge yet. Even more, if we are talking about teachers, they have not been trained and much less educated on this subject related to disabilities. Our university, and we consider that all other universities in our country, should ensure the inclusion of disabled people. “Being different is not the problem; the problem is being treated differently.”